2010
DOI: 10.1103/physrevb.82.184512
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the critical current in quasiperiodic pinning arrays below and above the matching magnetic flux

Abstract: Quasiperiodic pinning arrays, as recently demonstrated theoretically and experimentally using a fivefold Penrose tiling, can lead to a significant enhancement of the critical current I c as compared to "traditional" regular pinning arrays. However, while regular arrays showed only a sharp peak in I c ͑⌽͒ at the matching flux ⌽ 1 and quasiperiodic arrays provided a much broader maximum at ⌽Ͻ⌽ 1 , both types of pinning arrays turned out to be inefficient for fluxes larger than ⌽ 1 . We demonstrate theoretically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
4
48
2
Order By: Relevance
“…6 Unfortunately, at low temperatures, such PCs facilitate the proliferation of flux channeling [7][8][9][10] leading to unwanted instabilities of thermomagnetic origin 11,12 which render the superconductor impractical. A good compromise between strong pinning and lack of channeling can be achieved by introducing a quasiperiodic array of PCs, as suggested theoretically by Misko et al [13][14][15] and confirmed experimentally by Kemmler et al 16 and Silhanek et al 17 This aperiodic distribution of pinning centers may be further optimized by matching it to the typically non-uniform distribution of vortices. For instance, in order to create a distribution of PCs compatible with zero-field cooling conditions, one should then distribute them with a density gradient, decreasing from the edges toward the center of the sample, as expected for the vortex distribution of a partially penetrated sample in the mixed state according to the Bean model.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…6 Unfortunately, at low temperatures, such PCs facilitate the proliferation of flux channeling [7][8][9][10] leading to unwanted instabilities of thermomagnetic origin 11,12 which render the superconductor impractical. A good compromise between strong pinning and lack of channeling can be achieved by introducing a quasiperiodic array of PCs, as suggested theoretically by Misko et al [13][14][15] and confirmed experimentally by Kemmler et al 16 and Silhanek et al 17 This aperiodic distribution of pinning centers may be further optimized by matching it to the typically non-uniform distribution of vortices. For instance, in order to create a distribution of PCs compatible with zero-field cooling conditions, one should then distribute them with a density gradient, decreasing from the edges toward the center of the sample, as expected for the vortex distribution of a partially penetrated sample in the mixed state according to the Bean model.…”
mentioning
confidence: 86%
“…In fact, this subject remains timely and relevant for the present efforts to enhance the critical current density of superconducting materials. [13][14][15]31 In summary, we have demonstrated experimentally that, for low fields, a graded pinning landscape introduced in a superconducting film of a-Mo 79 Ge 21 increases the critical current, as compared to a uniform distribution of ADs. In addition, flux avalanche activity, typically induced by the presence of arrays of ADs, is less prejudicial for the sample with gradient distribution of antidots than for the uniformly distributed pinning centers.…”
Section: -mentioning
confidence: 99%
“…It was a delight to see how imaginative some applications may be, regarding for instance the storage of information in a Taylor approximant, using only a thermal excursion of the specimen placed in a magnetic field, presented by Janez Dolinsˇek [78], or how a thermal rectifier may be produced out of an ensemble of AlCuFe layers of adequately chosen conductivity, as show by Tsunehiro Takeuchi [79]. Finally, as mentioned above, mesoscopic systems like photonic quasicrystals [70] or superconductor arrays [71] may inherit interesting properties leading to an application when their internal structure is ordered quasiperiodically.…”
Section: New Applicationsmentioning
confidence: 99%
“…Applications based on artificial mesoscopic quasicrystals were also presented at the conference. For example, Xiangdong Zhang [70] described negative refraction metamaterials based on high-symmetry two-dimensional quasicrystals; and Vyacheslav Misko [71] showed how one could enhance the critical currents in superconductors by fabricating quasiperiodic pinning arrays at the nanoscale.…”
Section: Mesoscopic Quasicrystalsmentioning
confidence: 99%
“…If the APCs are arranged in a hexagonal or a rectangular lattice, the critical current is increased for certain magnetic matching fields due to the commensurability with the Abrikosov vortex lattice [1][2][3][4][5][6][7]. In order to increase the field range for vortex pinning, different APC distributions like quasiperiodic [8,9] or random [10,11] lattices have been investigated. Recent theoretical papers are focusing on non-uniform APC distributions like hyperbolic-tessellation arrays [12] and conformal crystals [13].…”
mentioning
confidence: 99%